Marginal Resection of Sacral Chordoma through Posterior Approach: Study of 18 Cases (TAJ: Journal of Teachers Association, 2018)
The study was carried out to report the results of marginal resection in sacral chordoma using a posterior midline approach. The study was carried out between July 2008 to June 2016, there were 21 patients who underwent the operation. Fourteen patients were male and seven were female and age ranging from 28 and 76 years. All most of the patients presented with pain, sacral mass and neurological deficit. Total sacrectomy and bone reconstruction were carried out in 11 patients. Subtotal sacrectomy was carried out in the remaining ten patients. Patients were followed up for at least seven years. Recovery after the operation was good. Duration of operation ranged between three to six hours. Three to five units blood was transfused in all patients after operation .Bowel and bladder dysfunction were almost all patients. After surgery following local complications including infection and wound disruption occurs in three patients and seroma occurs in two patients. Three patients (14%) had tumor recurrence and one patient expired three years after operation. 18 patients were still tumor-free at long term (seven years) follow-up. Marginal resection of sacral chordoma through posterior approachcan be a management plan for sacral chordoma with acceptable results.TAJ 2017; 30(1): 21-26